Tanshinone IIA Sodium Sulfonate Attenuates LPS-Induced Intestinal Injury in Mice - Xin-Jing Yang; Jin-Xian Qian; Yao Wei; Qiang Guo; Jun Jin; Xue Sun; Sheng-Lan Liu; Chun-Fang Xu; Guo-Xing Zhang (Gastroenterology Research and Practice)
Background. Tanshinone IIA sodium sulfonate (TSS) is known to possess anti-inflammatory effects and has exhibited protective effects in various inflammatory conditions; however, its role in lipopolysaccharide- (LPS-) induced intestinal injury is still unknown. Objective. The present study is designed to explore the role and possible mechanism of TSS in LPS-induced intestinal injury. Methods. Male C57BL/6J mice, challenged with intraperitoneal LPS injection, were treated with or without TSS 0.5 h prior to LPS exposure. At 1, 6, and 12 h after LPS injection, mice were sacrificed, and the small intestine was excised. The intestinal tissue injury was analyzed by HE staining. Inflammatory factors (TNF-α, IL-1β, and IL-6) in the intestinal tissue were examined by ELISA and RT-PCR. In addition, expressions of autophagy markers (microtubule-associated light chain 3 (LC3) and Beclin-1) were detected by western blot and RT-PCR. A number of autophagosomes were also observed under electron microscopy. Results. TSS treatment significantly attenuated small intestinal epithelium injury induced by LPS. LPS-induced release of inflammatory mediators, including TNF-α, IL-1β, and IL-6, were markedly inhibited by TSS. Furthermore, TSS treatment could effectively upregulate LPS-induced decrease of autophagy levels, as evidenced by the increased expression of LC3 and Beclin-1, and more autophagosomes. Conclusion. The protective effect of TSS on LPS-induced small intestinal injury may be attributed to the inhibition of inflammatory factors and promotion of autophagy levels. The present study may provide novel insight into the molecular mechanisms of TSS on the treatment of intestinal injury.